Pengembangan FLIPBOOK Berbasis Discovery Learning Berbantu Canva Pada Materi Usaha Dan Energi - Fitriani, Nurhikmah; U.S., Supardi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2025)
Information technology is developing rapidly in various aspects, including in the field of education, by utilizing smartphones, laptops, computers so that the learning process runs well. The results of the interview with the class From the results of the questionnaire for class Teachers and students hope for innovation in physics learning media in order to achieve the expected goals. This research aims to determine the feasibility of developing FLIPBOOK based on Discovery Learning assisted by Canva on business and energy material, as well as knowing students' responses to the media developed. This research uses the R&D (Research and Development) method with the development of the ADDIE model to the implementation stage. The results of this research obtained an average validation score of 86.50% by media experts 82%, material experts 85%, language experts 81% and education practitioners 98% with the category "very suitable" for use as learning media. Apart from that, it was implemented on 28 students and obtained an average student response score of 92% in the very good category.